Prioritization Model for IT Project Portfolio Management in Private University: A Literature Review - Rita Sari; Endang Sulistiyani; Nur Shabrina Meutia (Journal of Information System and Informatics, 2023)
The swift progress of technology can be harnessed to address the increasing demand for projects, particularly in various organizations like private universities that must cope with resource limitations and make critical decisions. Information Technology (IT) encompasses any technology, such as equipment or techniques, employed by businesses, institutions, or other organizations to process information, including computing, telecommunications technologies, consumer electronics, and broadcasting, as it increasingly digitizes. Choosing between dozens or hundreds of project alternatives presents complex multi-criteria decision-making problems for an organization's portfolio and priorities, necessitating clear-cut techniques, methods, and factor definitions for prioritizing decision-making. This literature review formulates the problem, specifically identifying the criteria for comparison and prioritization models, and seeks a framework and methodology for prioritizing portfolio management in private organizations, particularly universities. The literature review identifies the characteristics of private organizations and the methodologies and practices employed in researching the application of portfolio management priorities and explores the use of portfolio management techniques from prior studies tested in practice and project priority methodologies in private services. The results contribute to enhancing theories on techniques, methods, and, particularly, portfolio project management priorities for the private sector.